Custom TFT-LCD for avionics applications: Environmental tests and optical measurements. (February 2016) - Catelani, M.; Ciani, L.; Venzi, M.; Barile, G.
Highlights: A custom TFT-LCD display for avionics application is presented. Environmental requirements and test are discussed. Optical validation plan and measurements are described in detail. Abstract: Avionics represents of the most important industrial sector where innovation is a key issue. In order to guarantee that any new device introduced onboard has an adequate quality and reliability level, testing activity is fundamental to help engineers and technicians to verify their designs and prevent any safety critical failures. National regulatory agencies and standards organizations, such as, the European Union Authority for aviation safety (European Aviation Safety Agency – EASA), the United States defense standard, often called military standard (MIL-STD) carried out by the U.S. Department of Defense or the Radio Technical Commission for Aeronautics (RTCA), have developed several test procedures that have to manage with the customer requirements. This paper is focused on the experimental results related to the validation process of a custom TFT-LCD for avionics applications. Environmental tests and, in particular, optical measurements will be described in detail in order to underline the key role that test plannig and measurements represent in aerospace applications.